Public Employment and Governance in Middle East and North Africa - World Bank (World Bank, Washington, DC, 2016)
Government wage bills have been growing across the world, but are exceptionally high in the MENA region relative to countries’ state of development, whether measured as a share of GDP, or of government revenue and spending (World Bank, 2004). Across the region government wage bills threaten fiscal sustainability. There are many drivers behind the large wage bills, whether of central government alone or of general government. Government employment numbers also seem to grow inexorably, in many areas faster than required to deliver services in line with population growth. Other factors have been weak staff control systems, the authorization of new recruitment outside budget frameworks, and laxly applied staff performance assessment systems, in addition to absenteeism, and the difficulty under public service rules of disciplining and ultimately terminating poorly performing staff. This paper takes a look at government wage bill growth, alongside current approaches to recruitment, staff performance assessments and promotions, with particular emphasis on Egypt, Morocco and Tunisia. These country examples are complemented by a broader regional analysis to illustrate overarching trends in public sector employment.The objective is to identify the various forces at work, how they interact, and thereby document and understand better the dynamic of public sector wage bill expansion in the Middle East as well as potential linkages to public sector performance. The paper also looks at reform efforts, extracts lessons and identify potential reform options to better control wage bill growth and the unbalancing effects it has had on the efficiency and effectiveness of government spending generally. Furthermore, while the paper does not present a comprehensive overview of the nature of public employment in MENA, it aims to identify potential areas for further research in this domain.